Physicochemical, Microbiology, and Sensory Characterization of Goat Milk Kefir in Various Incubation Time - Sulmiyati Sulmiyati; Nur Saidah Said; Deka Uli Fahrodi; Ratmawati Malaka; Fatma Fatma (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
This study aimed to analyze the characteristics of goat milk kefir based on the incubation time variations on physicochemical, microbial and organoleptic. The method used was an experimental method using a Completely Randomized Design with 3 various incubation time which were for 12 hours, 18 hours and 24 hours with five replications. Parameters measured were physicochemical characteristics (pH, lactic acid concentration, and ethanol content), microbial characteristics which as the total number of lactic acid bacteria (LAB) colonies and the organoleptic characteristics were color, aroma, taste and favorability level towards goat milk kefir. Physicochemical and microbial data were analyzed by Analysis of Variance (ANOVA) while the organoleptic data were analyzed descriptively. The results showed that the incubation time gave significantly difference effect (P<0.05) on the pH, lactic acid concentration, the total number of LAB goat milk kefir and did not significant effect on the ethanol content. The organoleptic results showed that the incubation time didn’t significant effect on color and aroma, however gave significant affects on the tastes and favorability towards goat milk kefir. It can be concluded that the best incubation time was 24 hours. The physicochemical characteristics showed the pH value at 4.16±0.089; lactic acid concentration at 0.24±0.039%; ethanol content at 0.75±0.044%. The microbiology characteristics, the total number of Lactic Acid Bacteria at 1,24x107±0,008 CFU/ml. The characteristic of organoleptic color at 3.95 (white); aroma at 4.10 (kefir scent); taste at 4.25 (poor acid) and favorability at 4.15 (like).